SLOWLY BUT SURELY: THE MATERNAL PHASE OF SYLVIA PLATH IN HER LATE POEM - Adek, Muhammad (Elite : English and Literature Journal, 2022)
Being a mother is the most exclusive experience that only women experience. For centuries, women were forced to accept the dogma that motherhood is a wonderful experience. Silvia Plath, one of the female poets who dared to express her original experience of being a mother without having to follow the language of patriarchal literature. The Gynocritic approach is applied because it places the female voice as the single most original voice for the experience of motherhood without patriarchal interference. Several selected poems at the end of life from Silvia Plath were used as a source of research data. Research findings show that Plath had considerable difficulty in adapting to being a mother. Whatever experience Plath has, or any mother, is an exclusive wealth that should only be owned and shared by women.